Towards a global universal basic income for children - Blofield, Merike (2022)
Our policy brief directly addresses Germany’s G-7 priority of tackling issues of “particular global urgency .... to achieve tangible improvements for the people – within G7 countries and beyond, especially in newly industrialising and developing countries” by proposing a global basic income for all children. Even before COVID-19 hit, children were globally twice as likely as adults to live in extreme poverty, with long- term consequences for their life chances. During the past two years, the economic fall-out from the pandemic as well as school closures have further disproportionately hit children. Global shocks, whether pandemics or extreme weather conditions linked to climate change, are likely to only become more common, with negative shocks to our economies and social fabric, and ensuing humanitarian and migratory crises. We call for the establishment of a global universal basic income for all families with children, targeted preferentially via mothers, to ensure access to basic needs. This technically and fiscally feasible measure will have far-reaching benefits in the wellbeing and human capital of the next generation, directly addressing the G-7 policy priorities #2 (economic stability and transformation), #3 (healthy lives) and #5 (stronger together), and indirectly addressing priorities #1 (a sustainable planet) and #4 (investment in a better future). Furthermore, it will set a historical symbolic landmark: the beginning of a true sense of global citizenship where every child born will have his/her most basic needs guaranteed.